Is Aquaculture a Success? Evidence from Africa - Lubembe, Sharon Indasi; Okoth, Sharon; Hilda, R.B. Hounsounou; Turyasingura, Benson; Moenga, Kelvin O.; Mwalughali, Thoko B. S. (East African Nature and Science Organization, 2022)
Globally, human population growth worldwide is something that cannot be controlled, and so there is a need to sustain the needs of a growing population. In Africa, for instance, population projections are made yearly, not even once stagnation is seen. Feeding and nutrition issues, hunger eradication have become a problem with the continuing growth of the population, which in turn is putting a lot of pressure on available resources like capturing fisheries from the lakes, oceans, and rivers, leaving them void. Aquaculture has then proven useful in supplementing the dwindling catch fisheries stocks, which have become incapable of supporting the growing population. Since its introduction in Africa, however, changes have been seen as it has contributed to food security and malnutrition and improved livelihoods by creating jobs and generating income. Currently, diversified products come from aquaculture practices both in inland and freshwaters, ponds, and intensification of aquaculture farming methods, which all put together boost the production to a higher level. Genetics has also been employed to ensure seeds produced for aquaculture are worth being cultured for production. A lot of fisher folks are benefiting both directly and indirectly making a living. Although the contribution of aquaculture is small, sometimes termed insignificant, its growth is steady and it has a promising future as far as its goals (increased protein food production and improved livelihoods of fisher communities) are concerned